KESADARAN SEBAGAI PEMICU KEPATUHAN ATAS PENGENAAN SANKSI PAJAK KENDARAAN BERMOTOR DI KECAMATAN PARONGPONG - Ian Dogles Tampubolon; Mila Susanti (Jurnal Ekonomis, 2023)
The government's strategy in increasing revenue from motor vehicle tax through tax bleaching, name reversal exemption and tax payment discounts shows that motor vehicle tax revenue has still not reached the target. Therefore, this study aims to determine the compliance of motor vehicle taxpayers through tax sanctions triggered by taxpayer awareness. Using primary data through questionnaires. The study population is domiciled in Parongpong District, especially Cihanjuang Rahayu Village, Karya Wangi Village and Cihideung Village. Sampling through convenient sampling and found 65 respondents and processed with analysis of description, correlation, determination, and significance after normality tests. The results found that the relationship between low tax sanctions (r = 0.3411) with WPKB compliance, with a contribution of 11.6% and a partial significant effect (sig. 0.0054 < 0.05). The relationship between taxpayer awareness is very low (r = 0.1392) with mandatory PKB compliance, with a contribution of 1.9% and a partial insignificant effect (sig. 0.268 > 0.05). Simultaneously, it shows that significant tax sanctions (Sig. 0.0037 < 0.05) and taxpayer awareness are not significant (Sig. 0.1561 > 0.05) for WPKB compliance in Parongpong District. Thus, accepting Ho and rejecting Ha, it can be concluded that tax sanctions are not able to raise taxpayers' awareness to become compliant motor vehicle taxpayers.